Extractive Spectrophotometric Method for the Determination of Lamivudine and Zidovudine in Pharmaceutical Preparations Using Bromocresol Purple - Serife Evrim Kepekci Tekkeli (Journal of Chemistry)
A new spectrophotometric method has been established for the quantitation of lamivudine (LVD) and zidovudine (ZVD) in pharmaceutical preparations. The method is based on the reaction between the investigated drug substances and bromocresol purple (BCP) producing ion-pair complexes in acidic buffers which are suitable for chloroform extraction. The maximum absorbance of these complexes was measured at 424 nm in chloroform. All variables were studied to optimize the reaction conditions. Linearity ranges were found to be 25–250 μg mL−1 for LVD-BCP and 50–300 μg mL−1 for ZVD-BCP. The developed method was successfully applied for the determination of these drugs in pharmaceutical preparations. Excipients in pharmaceutical formulations did not interfere in the analysis. The results were compared statistically with those obtained by the HPLC method reported in the literature. According to the results, the proposed method can be recommended for quality control and routine analysis.